2020
DOI: 10.1177/0095327x20956722
|View full text |Cite
|
Sign up to set email alerts
|

Gender Mainstreaming in the Canadian Armed Forces and the Department of National Defence: Lessons on the Implementation of Gender-Based Analysis Plus (GBA+)

Abstract: This article uses the Canadian military’s gender-mainstreaming strategy—gender-based analysis plus (or GBA+)—as a case study to explore the implementation of gender mainstreaming in militaries. Utilizing a mixed method approach, including group interviews and surveys, we employ Jahan’s model of gender mainstreaming to understand how GBA+ has been operationalized. We argue that the implementation of GBA+ in the Defense Force constitutes a more superficial integrationist approach to the implementation of gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Hence, integrationist approaches are considered easier to implement as they only require women to be included into the prevailing system, rather than changing the existing structures of the organization (Tiessen, 2007). While Johnstone and Momani (2020) found that an integrationist approach could bring modest yet valuable changes to male-dominated organizations, they maintain that it cannot bring about fundamental changes to the prevailing culture.…”
Section: Transformative Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, integrationist approaches are considered easier to implement as they only require women to be included into the prevailing system, rather than changing the existing structures of the organization (Tiessen, 2007). While Johnstone and Momani (2020) found that an integrationist approach could bring modest yet valuable changes to male-dominated organizations, they maintain that it cannot bring about fundamental changes to the prevailing culture.…”
Section: Transformative Approachesmentioning
confidence: 99%
“…Gender mainstreaming has been put forward as a transformative approach to gender equality, particularly in military contexts (Caglar, 2013; Duncanson & Woodward, 2016; Rees, 2005). Gender mainstreaming gained prominence when the United Nations (UN) Security Council adopted Resolution 1325 on Women, Peace, and Security (WPS) in 2000, which called on member states to mainstream gender perspectives into all peacekeeping and security operations (Johnstone & Momani, 2020). The transformative potential of gender mainstreaming is linked to the promotion of gender equality and the incorporation of gender perspectives into planning and policymaking processes (UN, 1997).…”
Section: Transformative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…JECL was involved in the design and conceptualization of the work, analysis and to account for the unique challenges of individual Defence Team members in the development of organizational practices, policies and programs. 18 In particular, it is important for leaders of organizations to assess and understand the many ways in which diverse individuals might be impacted when facing a crisis, and to carefully consider this information when developing policies and support services to better serve all members of the workforce. Indeed, the present findings further illustrate how different sociodemographic groups may experience the same crisis in varying ways and thereby have distinct support needs.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The piecemeal integration and uptake of GBA+, both by key agencies and across departments, signals what is a broader issue in the policy space: critical analytical approaches, including intersectionality, are neither embraced across all policy areas, nor seen as legitimate within key disciplines that inform policymaking. For example, Johnstone and Momani (2022), in analyzing GBA+ uptake in military and defence policy, find among policy actors confusion about the purpose and implications of the tool, as well as concerns that GBA+ could compromise operational effectiveness. Further, outside of a small feminist branch, economists—who, for better or worse, enjoy a certain prominence in expert policy circles—have largely been absent from conversations about GBA+.…”
Section: Gba+ In Theory and Practice: Concerns And Criticismsmentioning
confidence: 99%